Transcutaneous Electrical Acupoint Stimulation Improved Preoperative Blood Pressure in Gynecological Malignant Tumor Patients With Hypertension: A Randomized, Controlled Trial - Chen, Liang; Shen, Yang; Liu, Shuangmei; Cao, Yanyan (Frontiers in Oncology, 2022)
Objective: Gynecological malignant tumor patients with hypertension, even if blood pressure is well controlled, are prone to hypertension before surgery. We plan to verify the effect of transcutaneous electrical acupoint stimulation (TEAS) on stabilizing blood pressure before operation. Methods: We enrolled 91 patients and randomly divided them into TEAS group (n=46) and control group (n=45). Patients in TEAS group received TEAS at acupoints Hegu and Neiguan. Patients in control group received transcutaneous electrical stimulation at the nonacupoint position of the upper limbs. After entering the operating room, the blood pressure before and after induction was measured. The main results were the occurrence of preinduction hypertension and postinduction hypotension. Results: There was no difference in the general information of the two groups. There were four cases (9%) of preinduction hypertension in TEAS group and 13 cases (29%) in control group. The incidence in TEAS group was significantly lower (P=0.013). There were five cases (11%) of postinduction hypotension in TEAS group and eight cases (18%) in control group. There was no significant difference between the two groups (P=0.346). The systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean blood pressure (MBP) of the highest blood pressure before induction in TEAS group were lower than those in control group (P=0.002, 0.002, and 0.001). There was no difference in SBP, DBP, or MBP between the two groups on the day before the operation. There was no difference in the lowest blood pressure before operation between the two groups after induction Conclusion: TEAS can prevent preinduction hypertension in patients with gynecological malignant tumors. Trial registration: ChiCTR2100054336, http://www.chictr.org.cn/showproj.aspx?proj=143276